Flow and sediment yield simulations for Bukit Merah Reservoir catchment, Malaysia: a case study - Abu Hasan, Zorkeﬂee; Hamidon, Nuramidah; Yusof, Mohd Sufﬁan; Ab Ghani, Aminuddin (IWA Publishing, 2012)
Bukit Merah Reservoir is the main potable and irrigation water source for Kerian District, Perak State, Malaysia. For the past two decades, the reservoir has experienced water stress. Land-use activities have been identiﬁed as the contributor of the sedimentation. The Soil and Water Assessment Tool (SWAT) was used to simulate and quantify the impacts of land-use change in the reservoir watershed. The SWAT was calibrated and two scenarios were constructed representing projected land use in the year 2015 and hypothetical land use to represent extensive land-use change in the catchment area. The simulation results based on 17 years of rainfall records indicate that average water quantity will not be signiﬁcantly affected but the ground water storage will decrease and suspended sediment will increase. Ground water decrease and sediment yield increase will exacerbate the Bukit Merah Reservoir operation problem.